Identificación de factores que influyen en la aparición de la caries de la lactancia - Buenaño L., Lucy Stella; Salcedo O., Olga Bibiana; Gómez de Arizmendi, Beatriz (Revista Estomatología, 1996)
The nursing caries is an oral pathology that affects children in early age, and its etiology is multifactorial. In this study, socioeconomic and cultural factors were analized, in relation with this type of caries; healthy children or children with nursing caries les s than 5 years old, were used for the study. The children belong to two population groups: Colsanitas prepayed health service and Comfandi ntributive health service in Cali , Colombia . The instrumentwas applied to 192 children were 89 had nursing caries and 103 were healthy a significant value was found after the estadistic analysis was made with SPSS and Epi-Info programs, in: Limit age at which the baby is fed with baby bottle, mothers atitudes while the baby is fed, why is the baby taken to the dentist, contradiction in the orders recieved by the people who take care ofthe baby, and social status study and age ofthe babys parents.